Citation Analysis as a Tool of Library Collections Evaluation - Hayati, Nurul (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2016)
This paper discusses about citation which one tool can be used in performing library collection evaluation. Throught this citation analysis, it can be known science growing and development in certain subject. In citation analysis also can be described relation between part or all document cited with citing document. So, it can be count how many the works cited by authors. For libraries, the result of citation analysis can become consideration in making collection development policy.